Chemical Investigation of Mesua nagassarium (Burm. f.) Kosterm - Ridwan Islam; Iftekhar Ahmed; Al Amin Sikder; Mohammad Rashedul Haque; Abdullah Al-Mansur; Mansoor Ahmed; Munawar Rasheed; Mohammad A. Rashid (Journal of Basic & Applied Sciences, 2021)
Repeated chromatographic separation and purification of pet-ether and carbon tetrachloride soluble fractions of a methanol extract of stem bark of Mesua nagassarium (Burm. f.) Kosterm yielded five compounds. Extensive spectroscopic studies, including high field NMR analyses was conducted to identify these compounds which resulted to be friedelin (1), 3β-friedelanol (2),lupeol (3), 3-oxo-betulin(4) and spinasterol (5). Although compounds 1–3have been reported from various plant species, but 3-oxo-betulinand spinasterol have been discovered from M. nagassarium (Burm. f.) Kosterm for the first time.